2010
DOI: 10.1021/jo101223z
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Cross-Coupling Reactions of Boronic Acids with Dihalo Heterocycles

Abstract: The carboxylic acid anion moiety has been used as a tunable directing group in the cross-coupling reaction of 2,6-dichloronicotinic acid and 2,5-dibromo-1,2,4-triazole derivatives producing selectively the 2- or 6-substituted nicotinic acids, while only the 5-substituted triazoles were obtained under a variety of conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…[106][107][108] Using the Handy and Zhang method, many effective regioselective cross-couplings on polyhalogenated pyridines have been performed. [108][109][110][111][112][113] In continuation of the study on site-selective arylation on nicotinic acid derivatives, 114,115 additional examples of highly regioselective cross-coupling reaction of boronic acids with 2,6-dichloronicotinic acid (89) were presented by Houpis and co-workers in 2010. 109 The cross-coupling reaction with arylboronic acids having both electron-withdrawing and electron-donating substituents afforded the products in good yields and excellent selectivity (Scheme 13).…”
Section: Site-selective Synthesis Of Arylpyridinesmentioning
confidence: 99%
“…[106][107][108] Using the Handy and Zhang method, many effective regioselective cross-couplings on polyhalogenated pyridines have been performed. [108][109][110][111][112][113] In continuation of the study on site-selective arylation on nicotinic acid derivatives, 114,115 additional examples of highly regioselective cross-coupling reaction of boronic acids with 2,6-dichloronicotinic acid (89) were presented by Houpis and co-workers in 2010. 109 The cross-coupling reaction with arylboronic acids having both electron-withdrawing and electron-donating substituents afforded the products in good yields and excellent selectivity (Scheme 13).…”
Section: Site-selective Synthesis Of Arylpyridinesmentioning
confidence: 99%
“…[178] Changing the ligand and Pd sources affect the switch in chemoselectivity: the more bulky ligand directs an oxidative addition at the less hindered para position while oxidative addition is irreversible at the ortho position for a system without a similar ligand (also Class B divergence). This concept has also been successfully applied to site-selective cross-coupling of boronic acids and dichloro heterocycles such as 184 (Scheme 45 d) [179] and site-selective monoamination of dibromobenzoic acid 183 with Pd versus Cu catalysts (Scheme 45 e). [180]…”
Section: Catalytic Chemoselective Arene Functionalizationsmentioning
confidence: 99%
“…However, the weak reactivity of C-substitution on triazole ring due to lower electronegativity in contrast with nitrogen atoms results in the few developments of C-substitution. Recently, researches have found that the metal catalyzed coupling reaction as a classical synthetic strategy can efficiently realize C-substitution on triazole ring, and much effort has been contributed to widen the application scope of C-C cross coupling reactions on aryl rings [283][284][285][286][287][288][289], especially on 1,2,4-triazole ring in organic chemistry. The reported C-substitution on 1,2,4-triazole ring is systematically involving cleavage of C-H and C-X bonds.…”
Section: C-substitution Of 124-triazole Ringmentioning
confidence: 99%